Comparison of positional distraction with stabilisation exercises versus stabilisation exercises alone in the management of lumbar radiculopathy. A randomized controlled-trial - Khan, Salman; Farheen Hasnain; Rabail Rani Soomro; Asim Rehmani (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the effects of positional distraction with stabilisation exercises versus stabilisation exercises alone in the management of lumbar radiculopathy. Method: The randomised controlled trial was conducted from July to December 2020 at the Institute of Physical Medicine and Rehabilitation, Dow University of Health Sciences, and the Neurosurgery ward of Civil Hospital, Karachi, and comprised individuals of either gender with lumbar radiculopathy pain who were randomised into positional distraction with stabilisation exercises group A and stabilisation exercise group B. The treatment duration was 3 sessions per week for 8 weeks. Intensity of pain and disability were assessed using the Visual Analogue Scale and the Roland Morris Disability Questionnaire, respectively. Data was analysed using SPSS 21. Results: Of the 100 patients, 63(63%) were males and 37(37%) were females. Overall, 89(89%) were married. There were 50(50%) subjects in group A with mean age 39.42±6.36 years and 50(%) in group B with mean age 38.80±6.69 years. There was no significant difference in terms of age, gender and marital status between the groups (p>0.05). The study was completed by 96(96%) patients; 48(50%) in each of the 2 groups. Intragroup improvement post-intervention compared to baseline was significant (p<0.001) in both groups. Outcomes in group A were significantly better than in group B (p<0.05). Conclusion: Addition of positional distraction to stabilisation exercises was found to have superior effects compared to stabilisation exercise alone on pain and functional disability among patients with lumbar radiculopathy. Clinical Trial Number: NCT04427423 dated 27th April 2020. Key Words: Low back pain, Exercise therapy, Radiculopathy, Sciatica, Traction.